The Effect of Workplace Romance on Job Performance Mediated by Job Engagement Among Employees: Case Study From PKU Muhammadiyah Hospital Surabaya, Indonesia - Abdalla, Pasha Arief; Agustina, Tri Siwi (Golden Ratio of Human Resource Management, 2025)
This study investigates how the workplace affects job performance through employees' job engagement at PKU Muhammadiyah Hospital Surabaya. Using a quantitative explanatory methodology, the research utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS), used in this work via SmartPLS software. A structured survey was used to gather information from 141 workers. The findings reveal a positive relationship between workplace romance and job performance, with a path coefficient of 0.132. A positive relationship between workplace romance and job engagement, with a path coefficient of 0.650. There is a positive relationship between job engagement and job performance, with a path coefficient of 0.780. A positive relationship between workplace romance and job performance through job engagement of employees at PKU Muhammadiyah Hospital Surabaya, with a path coefficient of 0.507.